2021
DOI: 10.1007/978-3-030-82014-5_18
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Optimal Control of a Vessel with Redundant Structure of Executive Devices

Abstract: The article considers the issues of automatic control of the vessel movement with a redundant control structure. Redundant structures are now widely used on all vessels with a dynamic positioning system to improve control efficiency (accuracy, maneuverability, reduce energy consumption and emissions), reliability and environmental safety. A brief review of the literature on the use of redundant structures to improve control efficiency is made. In open sources, the authors have not found solutions that improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The obtained result of increasing the control moment, speed of rotation and reducing the time for turning the vessel is explained by the optimization of the control moment in the redundant structure [9]. This is achieved by: using an on-board calculator; solving, at each step of the on-board computer, an optimization problem with a non-linear objective function, linear and non-linear control constraints; transfer of optimal controls to the automation of executive devices for testing.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained result of increasing the control moment, speed of rotation and reducing the time for turning the vessel is explained by the optimization of the control moment in the redundant structure [9]. This is achieved by: using an on-board calculator; solving, at each step of the on-board computer, an optimization problem with a non-linear objective function, linear and non-linear control constraints; transfer of optimal controls to the automation of executive devices for testing.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of the study, statistical data were calculated and identified, which reveal the dependence between the MMS of navigators and the sequence of their actions when performing sea maneuvers [20,21]. It should be emphasized that one of the available results was the clustering of naval teams according to typical patterns of behavior in relation to MMS.…”
Section: The Study Materials and Methodsmentioning
confidence: 99%